Comprehensive revision of Lycogala (Myxomycetes) in subtropical China: morphological and phylogenetic insights and ten new species - Wen-Long Song; Zi-Qiong Jiang; Min Li; Dmytro Leontyev; Yang Gao; Shuang-Lin Chen (IMA Fungus)
In recent years, significant advancements have been made in the taxonomy and phylogenetics of Lycogala, leading to the description of numerous new species. However, Lycogala in China has never been systematically revised, and only eight species have been recorded. In this study, specimens of Lycogala from 22 sites in 11 provinces or cities of subtropical China were studied in terms of morphology, two-gene phylogenetic analysis (nuclear 18S rDNA and cytochrome oxidase subunit I), and ASAP species delimitation. We provide a checklist, which includes 21 species of Lycogala collected in subtropical China. These species include (1) seven species already known from the country, for which we report new localities, (2) four species, new to China (Lycogala alisaulianovae, L. fossiculatum, L. skovorodaense, and L. succineum) and (3) ten species new to science, including L. annulatum sp. nov., L. chinense sp. nov., L. convexum sp. nov., L. fasciculovesiculiferum sp. nov., L. helvolum sp. nov., L. indirubinum sp. nov., L. nigrum sp. nov., L. planovesiculiferum sp. nov., L. projectum sp. nov., and L. uviforme sp. nov. A comprehensive morphological description, detailed illustrations, molecular barcoding data, and putative position in phylogenies are provided for the newly described taxa.